Sacco and Vanzetti : the anarchist background - Avrich, Paul (Princeton University Press, 1991)
An in-depth study of the lives of Nicola Sacco and Bartolomeo Vanzetti, based on anarchist sources and new materials, provides answers to crucial questions about one of the most notorious cases in American legal history. Bibliog.